Source Credibility Assessment in the Realm of Information Disorder: A Literature Review - Cosentino, Alessia; de Maio, Carmen; Furno, Domenico; Gallo, Mariacristina; Loia, Vincenzo (UNIR, 2026)
The proliferation of information disorder in the digital age has sparked a growing concern regarding the credibility of sources disseminating information. This review examines the evolving landscape of source credibility within information disorder. The review synthesizes key findings and trends related to the factors influencing source credibility, including available tools, shared indicators, and existing methods experimented with in calculating source credibility. The analysis highlights that from a more commercial point of view, several tools are aimed at analyzing the content’s credibility and studying the sources’ credibility. However, from a methodological point of view, there is still something more to do. Indicators that can be used to carry out a source credibility assessment focus on the structure and design of the source, excluding others indicating how the page traffic could be. As for the techniques to be used to assess the credibility of a source, it emerged that more innovative techniques, such as deep-learning, are being developed alongside slightly more classical statistical methods. The review analyzes 23 papers from Conferences and 22 from Journals published in recent years. It also identifies avenues for future inquiry and the development of effective strategies to combat the challenges posed by misinformation in the digital era.
Keywords: credibility assessment; information disorder; reliability; source